Post-Brexit Britain from the Satirical Gaze of Sam Byers’ Perfidious Albion - Elices, Juan F. (Complutense Journal of English Studies, 2023)
2016 marks a decisive turning point in Europe’s recent history. On June of that same year, a referendum was called to decide whether the country should remain or leave the European Union. Although many analysts, commentators and even colleagues in the EU saw this as a bizarre move, the results unearthed the polarization that has historically underlain the country and the unresolved divide between two clearly unreconciled positionings. The re-emergence of a discourse, epitomized by Nigel Farage’s UKIP deeply permeated some sectors of the British society and brought back a movement that longed for reinstating the country’s imperial past and its most self-isolationist claims. It is this context of political turmoil and growing racial tension that writers like Jonathan Coe or Sam Byers tackle in novels such as Middle England (2018) and Perfidious Albion (2018), respectively. Focusing particularly on Byers’ work, his satirical approach to Brexit enables him to build up a society in which readers witness the rise of media totalitarianism and the control of dissenting voices through an intricate network of hi-tech corporations. Bearing all this in mind, the aim of this paper will be, first, to explore the ways Perfidious Albion satirizes the ideological foundations of populism on which Brexit was sustained and, secondly, to delve into the apparatus of rhetorical devices the author draws on in order to address his criticism.